Modern Millenarianism in Philippines and the State: Focus on Negros, 1857-1927 - Bauzon, Leslie (Philippine Social Sciences Review; The Revolution of 1896 and the Continuing Struggle for National Dignity and Solidarity, Ed., Gil G. Gotiangco, 2010)
This paper aims to show concrete manifestations of social and religious unrest in Negros Island, Visayas Philippines, covering a 70-year period marked by a movement now known as Babaylanism. The year 1857 witnessed the blood-drenched tragedy that was the Manyabog Affair while 1927 marked the occurrence of the farcical Entrencherado Uprising. Spanish colonial rule in the Philippines wag established in 1565 and formally ended in 1898 with Spain's cession of the Philippine Islands to the United States of America by the terms of the Treaty of Paris, concluded and signed by the two countries on 10 December 1898. The Treaty of Paris ended what erupted in early 1898, two years after the Filipinos initiated their struggle for national emancipation from Spanish political yoke. This presentation covers the final four decades of the Castilian regime in the Islands and nearly the whole initial generation of American colonial dominance.